Constitutions of Deficiency and Stasis of Traditional Chinese Medicine and Related Factors among Middle-Aged Women in Taiwan. (20th October 2020) - Chen, Ping-Ho; Huang, Sheng-Miauh; Lai, Jerry Cheng-Yen; Yu, Pei-Jung
Abstract : Background . Traditional Chinese medicine (TCM) appears to be the common therapy in middle-aged women. The constitution serves as a guide for TCM treatment. However, little is known about the constitution and related factors in middle-aged women. The objectives of this study were to describe the yang-deficiency, yin-deficiency, and stasis constitutions in middle-aged women. Demographic and health factors related to yang deficiency, yin deficiency, and stasis were also examined. Methods . A total of 1, 000 women aged 40–65 years were selected from 2009 through 2018 using random sampling from the Taiwan Biobank Research Database in Taiwan. Yang-deficiency, yin-deficiency, and stasis were assessed using the body constitution questionnaire. Multiple logistic regression analysis was used to identify factors associated with constitution in deficiency or stasis. Results . The proportions of middle-aged women who had the constitution in yang-deficiency, yin-deficiency, and stasis were 29.7%, 21.7%, and 17.7%, respectively. The result of binary logistic regression showed that current menstruation, abnormal spirometry, and education level were predictive factors of yang deficiency. Women with younger age, abnormal spirometry, or a vegetarian diet had a significantly associated yin deficiency. Younger age, abnormal spirometry, and coffee habit were predictors of stasis. Conclusions . Middle-aged women in Taiwan with abnormal spirometry had a higher risk for deficiency or stasis constitutions, especially for those younger than 56 years. Healthcare providers should learn patients' constitutions and provide appropriate advice, referring them to safe providers of their desired method.